2015
DOI: 10.1002/cm.21260
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of procentrioles in Drosophila spermatids

Abstract: Male gametogenesis in insects is unusual in that the centrioles do not duplicate during the second meiosis and the differentiating spermatids inherit only one centriole. Here it is showed that a distinct procentriole is assembled close to the proximal region of the centriole in early S13 spermatids at the onion stage, confirming previous reports of a proximal centriole-like structure at the proximal end of the spermatid centriole. However, the procentrioles of Drosophila spermatids do not behave like true proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…A similar enigma existed previously in insects until it was shown that insect sperm possesses, in addition to the known centriole, a second atypical centriolar structure 1416 . This atypical structure has been shown to be essential for normal fertility and embryo development 15,17 .…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…A similar enigma existed previously in insects until it was shown that insect sperm possesses, in addition to the known centriole, a second atypical centriolar structure 1416 . This atypical structure has been shown to be essential for normal fertility and embryo development 15,17 .…”
Section: Introductionsupporting
confidence: 55%
“…However, recently a second centriole that is atypical was described in insect sperm 15,16,25,42 . Similarly, here we show that mammalian sperm also have one typical and one atypical centriole.…”
Section: Discussionmentioning
confidence: 99%
“…Close to the basal body of spermatids, there is a small disk of dense material, the “proximal centriole-like” or PCL (Blachon et al 2009; Gottardo et al 2015c), that may represent the origin for the second centriole in the Drosophila zygote (Blachon et al 2014; Khire et al 2016). PCL formation depends on Plk4, Sas-6, and Poc1, and the PCL contains many centriolar proteins that include Sas-6, Ana1, and Bld10p/Cep135 (Blachon et al 2009).…”
Section: When the Centriole Becomes The Basal Body: Ciliogenesismentioning
confidence: 99%
“…An unexpected centriole duplication is also observed in early spermatids of some insect species in which a structurally distinct procentriole is observed close to the proximal region of the basal body at the beginning of the axoneme elongation ( Figure 6B,C) [96,122,123]. The assembly of these procentrioles requires in Drosophila typical centriolar proteins, such as Ana1, Bld10/Cep135, Sak/Plk4 and Sas6 [82,124,125].…”
Section: Centriole Overduplication In Insects: Breaking the Rulesmentioning
confidence: 72%